"You've Got to Do Something": Developing Occupational Therapists' Role in End-of-Life Care. (January 2023) - Chow, Janice Kishi; Pickens, Noralyn Davel; Fletcher, Tina; Thompson, Mary; Bowyer, Patricia
Occupational therapists support the occupational participation of people who are dying yet remain underutilized in end-of-life care. The purpose of this article was to explore how occupational therapists develop their role in end-of-life care to provide strategies to address underutilization. Using a grounded-theory method, semi-structured interviews were conducted with 21 occupational therapists. Three themes emerged which demonstrate participants' role development process. Participants' experiences with dying (Close Experience of Loss) often instilled the importance of end-of-life care. Led by these convictions (Willing to Do It), participants developed skills for end-of-life care. Reflecting on their experiences and treatment outcomes (Making a Difference), participants self-validated their role. The Model of Occupational Therapists' Role Development in End-of-Life Care captured this process. Personal experiences and critical self-reflection may provide an adaptive means to drive role development and appropriately increase end-of-life care occupational therapy utilization.